Utility of sequential organ failure assessment score in prognosticating sick children in pediatric intensive care unit - Gogia, Priya; Prasad, Sunita (International Journal of Contemporary Pediatrics, 2016)
Background:This study was designed to assess the utility of sequential organ failure assessment score (SOFA) score as a predictor of mortality in pediatric intensive care unit (PICU). Methods: A prospective hospital based study was carried out in PICU of Gajra Raja medical college, Gwalior, Madhya Pradesh, India. Critically ill patients admitted to PICU were recruited and followed up until they were discharged or deceased. The SOFA score was calculated for all the subjects during first 24 and 72 hours and difference between both i.e. delta SOFA was calculated. Results:The mean SOFA at 72 hours (T72) was 15.63±2.98 in non-survivors vs. 4.30±2.54 in survivors and was significantly higher (P<0.001). The negative and positive predictive values of SOFA at T 72 were comparable to pediatric logistic organ dysfunction (PELOD) score while these values were less for initial SOFA and delta SOFA score. Conclusions:Out study showed that SOFA T72 is a better predictor of mortality as compared to initial and delta SOFA score. The SOFA T 72 is comparable to PELOD score and can be used as a reliable predictor of mortality in children.